W oczekiwaniu na ostateczne rozstrzygnięcie. Bydgoszcz i bydgoszczanie w okresie od zaakceptowania warunków traktatu wersalskiego przez Niemcy w świetle „Dziennika Bydgoskiego”, „Bromberger Tageblatt” i „Bromberger Zeitung” (Tabularium Historiae, 2020)
The article presents the events that took place in Bydgoszcz between June 1919 and January 1920. The author presents them in the light of the local press: the Polish-language “Dziennik Bydgoski” and the German-language “Bromberger Tageblatt” and “Bromberger Zeitung”. The text focuses on topics related to social life in the press at that time, including how the nationally heterogeneous society of Bydgoszcz perceived the provisions of the Versailles Treaty. The tension caused by the disagreement of various national and political groups with the post-war arrangements led to many incidents, which were widely commented on by the local media. The key issues discussed by the Bydgoszcz newspapers were the final territorial arrangements and considerations about the future of the city. The roundbreaking decisions made in Paris meant joy for Poles, and for Germans mourning.